Development of Criteria for a Positive Front-of-Package Food Labeling: The Israeli Case - Gillon-Keren, Michal (Nutrients, 2020)
Efforts to shape the food environment are aimed at reducing diet-related co-morbidities. Front-of-package labeling (FOPL) may support the consumers to make an informed decision at the point of purchase and encourage industry to reformulate food products. The Israeli Ministry of Health (MOH) implemented a unique FOPL system, using two colors: A mandatory warning (red) label alongside a voluntary positive (green) label. An independent Scientific Committee, from academia, the healthcare system, and MOH was appointed to determine the core principles for the positive FOPL. The criteria were based on the Mediterranean diet principles, with adjustments to the Israeli dietary habits, focusing on the health advantages of the food and considering its processing level. The food products eligible for positive FOPL are foods in their natural form or with added spices or herbs, or those that underwent minimal processing, with no food additives. Based on population consumption data, 19.8% of food products were eligible for positive FOPL; of them, 54% were fruits and vegetables, 20% dairy, and 14% grains. An evaluation plan is needed to assess the degree of acceptance of the positive FOPL by the industry, retailers, and the public, and its impact on food consumption and on public health.